The Lulo Dance from Traditional to MURI Record: Historical Analysis of Tolakinese Culture in Southeast Sulawesi, Indonesia - Melamba, Basrin; Syukur, La Ode; Nggawu, La Ode (TAWARIKH, 2015)
ABSTRACT: Southeast Sulawesi is one of the provinces in Indonesia, with a population that inhabit this region divided into several ethnics, such as Tolakinese (consisting Tolaki Konawe and Mekongga), Moronenese, Wunanese (Muna), Wolionese (Buton), Wawonii, Erekenese (Kulisusu), Javanese, and Torajanese. This paper is analyzing âluloâ dance related with cultural activity of the Tolakinese people. The birth of âluloâ dance is really close with the activity of Tolakinese people in agriculture area. âLuloâ dance has been developed and changed since traditional empire era until now, which is this dance success in winning the record of MURI (Musium Rekor Indonesia or Indonesia Record Museum) in Indonesia. The development such as music background, the equipment, meaning and function of the dance, movement, costume, and etiquette, included the types of âluloâ dance itself. âLuloâ always stand and survive to show it existence as a medium of entertainment, because of âluloâ dance is easy to learn. âLuloâ dance typical is relative and flexible, it is not limited by space, time, clothes, music background, included the participant. âLuloâ dance can be performed by anyone that come from different social class in the community. âLuloâ dance is always adaptive with the development of ages. âLuloâ dance has variety in it, it is relating to the music background, movement, region, and the person who created it. The âluloâ dance had became a popular culture, especially dances in Southeast Sulawesi, Indonesia.KEY WORDS: The âluloâ dance, Tolakinese culture, Southeast Sulawesi, agriculture area, medium of entertainment, easy to learn, and historical analysis.Â Â Â Â About the Authors: Basrin Melamba is a Lecturer at the Department of History, Faculty of Humanities UHO (University of Halu Oleo) in Kendari 93232, Southeast Sulawesi, Indonesia; La Ode Syukur and La Ode Nggawu are the Lecturers at the Department of Language and Arts, Faculty of Education and Teacher Training UHO in Kendari 93232, Southeast Sulawesi, Indonesia. E-mails address: melambabasrin@yahoo.com and awu_fan@ymail.comHow to cite this article? Melamba, Basrin, La Ode Syukur & La Ode Nggawu. (2015). âThe Lulo Dance from Traditional to MURI Record: Historical Analysis of Tolakinese Culture in Southeast Sulawesi, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.87-98. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (April 21, 2015); Revised (June 17, 2015); and Published (October 28, 2015).